PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, PERSEPSI HARGA, DAN ASOSIASI MEREK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN - Agus Wijaya (Jurnal Bisnis Terapan, 2018)
This is a case study to explain the causal relationship between the variables in the research model, namely product quality, service quality, price perceptions, and brand association to customer satisfaction, and customer loyalty. The research was conducted by distributing questionnaires to 130 people who have two or more Honda motorcycles in the last 5 years in Surabaya, then processed using Stuctural Equation Modeling (SEM) method with the help of AMOS 20.0 software. The result of research indicated that the direct effect of product quality to customer loyalty is 0.270, while the influence of product quality to customer loyalty indirectly through customer satisfaction mediation is 0.102. The value of the direct effect of product quality on customer loyalty is greater than the indirect effect. The results showed that there is no direct effect of service quality on customer loyalty because the value is very small that is 0,065, while the influence of service quality to customer loyalty indirectly through customer satisfaction mediation is also very small that is equal to 0.049. The direct effect of price perception on customer loyalty is 0.236, while the effect of price perception on customer loyalty indirectly through customer satisfaction mediation is 0.064. The direct influence of brand association to customer loyalty is 0.318, while the influence of brand association to customer loyalty indirectly through customer satisfaction mediation is 0.041.